Epidemiological profile of stroke in the State of Amapá, Brazil (Research, Society and Development, 2020)
Stroke is one of the most important public health problems worldwide, being the second most common cause of death in the world, and also responsible for a large number of hospitalizations, disability and some form of disability. The objective of the article is to describe the epidemiological profile of patients hospitalized with stroke in the State of Amapá, from January 2010 to December 2019. This is a retrospective, quantitative, ecological study that collected data from information provided in sih / datasus. The epidemiological variables investigated were: number of hospitalizations, sex, ethnicity, age group and number of deaths. The study identified that a total of 3103 patients were hospitalized with stroke. The male gender prevailed with 55.46% of the cases. Regarding ethnicity, browns were the most affected (87.09%). The age group of 70 years or more prevailed (49.11%). An annual increase in stroke mortality was observed in the 10 years analyzed, with the highest number of deaths (96) in 2019. Therefore, it is essential that stroke prevention measures be intensified through improvements in the control of the modifiable risk factors. To this end, it is essential that there is a better training of health professionals, especially the those who work in Primary Care, in order to be more prepared to treat the diseases that increase the risk of stroke.